2014 14th IEEE/ACM International Symposium on Cluster, Cloud and Grid Computing 2014
DOI: 10.1109/ccgrid.2014.19
|View full text |Cite
|
Sign up to set email alerts
|

NoCMsg: Scalable NoC-Based Message Passing

Abstract: Abstract-Current processor design with ever more cores may ensure that theoretical compute performance still follows past increases (resting from Moore's law), but they also increasingly present a challenge to hardware and software alike. As the core count increases, the network-on-chip (NoC) topology has changed from buses over rings and fully connected meshes to 2D meshes. The question is which programming paradigm provides the scalability needed to ensure performance is close to theoretical peak, where 2D m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Our study is based on native shared memory at the DRAM level that does not require load/stores to be rewritten, nor is it restricted to 8KB shared data. We recently ported NoCMsg to the Intel SCC [Patil 2014] and found that our flow control elimination in conjunction with contention-free communication patterns provide similar performance improvements on the Intel SCC compared to the Tilera [Zimmer and Mueller 2014;Yagna 2013].…”
Section: Related Workmentioning
confidence: 66%
“…Our study is based on native shared memory at the DRAM level that does not require load/stores to be rewritten, nor is it restricted to 8KB shared data. We recently ported NoCMsg to the Intel SCC [Patil 2014] and found that our flow control elimination in conjunction with contention-free communication patterns provide similar performance improvements on the Intel SCC compared to the Tilera [Zimmer and Mueller 2014;Yagna 2013].…”
Section: Related Workmentioning
confidence: 66%
“…The User Dynamic Network (UDN) interconnect is the only one available for user-generated messages. We use the services of the NoCMsg [33] library. NoCMsg provides a deadlock free, scalable and efficient low-level message passing layer over UDN with an MPI like interface.…”
Section: Methodsmentioning
confidence: 99%
“…With SSI, resources are aggregated to present a single view of the operating system environment while data access and communication are realized via shared memory over traditional bidirectional buses. This approach delivers some performance increases in the natural evolution from single core up to 16 cores, but it deteriorates rapidly when the number of cores increases further [33].…”
Section: Scalability Challenges Of Large-scale Manycoresmentioning
confidence: 99%
See 2 more Smart Citations